The Political Use of Evidence and Its Contribution to Democratic Discourse. (2nd March 2018) - Schlaufer, Caroline; Stucki, Iris; Sager, Fritz
Abstract: This article argues that evidence, even when used politically, contributes to high‐quality democratic discourse. Research results on the use of evidence in referendum campaigns in Switzerland show that (1) evidence fosters discourse quality and shifts the focus away from politics to policy; (2) evaluations and basic research contribute positively to discourse, but not opinion surveys and statistics; (3) the participation of experts and administrative practitioners in discourse is crucial to make evidence available to the public; and (4) evidence is always used as a part of a narrative and can alter the constructed images used in a story. In conclusion, the implications for practitioners are discussed .